Improving Cattle Farmers Knowledge of Animal Weight Monitoring Using IoT: Peningkatan Pengetahuan Peternak Sapi dalam Monitoring Berat Badan Hewan Ternak Berbasis IOT - Wahyu Andi Saputra; Muhamad Azrino Gustalika; Faizah Faizah; Silvia Van Marsally; Dedy Agung Prabowo; Fahrudin Mukti Wibowo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The Mukti Mandiri Livestock Group is located in Karanggitung Village, Banyumas Regency. This group focuses on beef cattle farming. Currently, the group faces various obstacles, including the lack of ability to accurately calculate cattle weight. This causes the group to often rent scales or entrust their cattle to other cattle groups to determine their weight. Furthermore, the Mukti Mandiri Group often chooses to estimate the weight of cattle due to the high rental price of scales. This impacts the selling price of cattle to collectors, resulting in farmers only earning a small profit. Therefore, a weighing device is needed to assist the Mukti Mandiri Livestock Group. This community service activity was carried out in order to provide IoT (Internet of Things)-based weighing devices to facilitate the cattle weighing process. The activity consisted of 5 stages: socialization, technology implementation, training, mentoring and evaluation, and the sustainability of the community service program. The results of this community service showed that 51% of respondents answered strongly agree, 46% agreed, and 3% quite agreed, in terms of increasing the knowledge of livestock farmers regarding the community service activity and the use of IoT-based weighing devices. It is hoped that this community service activity can continue in the management aspect for RPH (Animal Slaughterhouse) and Juleha (Halal Slaughterhouse) so that it can encourage participation from other livestock breeders in the use of technology in the livestock sector.